2008
DOI: 10.1371/journal.pone.0002619
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference and Body Mass Index as Predictors of Health Care Costs

Abstract: BackgroundIn the present study we analyze the relationship between body mass index (BMI) and waist circumference (WC) and future health care costs. On the basis of the relation between these anthropometric measures and mortality, we hypothesized that for all levels of BMI increased WC implies added future health care costs (Hypothesis 1) and for given levels of WC increased BMI entails reduced future health care costs (Hypothesis 2). We furthermore assessed whether a combination of the two measures predicts he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
5
30
0
1
Order By: Relevance
“…It has been shown that WC more precisely identifies highrisk individuals by pinpointing those with a high body fat content and an increased intraabdominal accumulation of fat [37]. This result is supported by a study based on the same data as in this article, which demonstrates that WC is a better predictor of future health care costs than BMI [38]. Two health economic studies [10,12] found increased costs associated with increased WC, but limitations of their study design makes it difficult to derive generally applicable estimates of the health care costs.…”
Section: Introductionsupporting
confidence: 79%
“…It has been shown that WC more precisely identifies highrisk individuals by pinpointing those with a high body fat content and an increased intraabdominal accumulation of fat [37]. This result is supported by a study based on the same data as in this article, which demonstrates that WC is a better predictor of future health care costs than BMI [38]. Two health economic studies [10,12] found increased costs associated with increased WC, but limitations of their study design makes it difficult to derive generally applicable estimates of the health care costs.…”
Section: Introductionsupporting
confidence: 79%
“…Considering that BMI is a proxy measure of total body fat, whereas WC is a proxy measure of abdominal fat mass, the combination of the two measures have been suggested since it might represent a better predictor to assess risks associated with excess adiposity (Freiberg et al, 2008;Hojgaard et al, 2008). In our study, using BMI and WC together we observed a higher prevalence of women at risk (28%) when comparing to men (18%).…”
Section: Discussionmentioning
confidence: 50%
“…82 Waist circumference, a surrogate marker of abdominal obesity, further predicts healthcare costs beyond BMI. 83 Obesity is also associated with significant increases in indirect costs such as …”
Section: Costmentioning
confidence: 99%